(untitled) (Communications in Mathematical Research, 2019)
In this article, we extend some estimates of the right-hand side of the Hermite-Hadamard type inequality for preinvex functions with fractional integral. The notion of logarithmically s-Godunova-Levin-preinvex function in second sense is introduced and then a new Hermite-Hadamard inequality is derived for the class of logarithmically s-Godunova-Levin-preinvex function.